FINITE TIME THERMODYNAMICS AND THE QUASI-STABILITY OF CLOSED-SYSTEMS OF NATURAL HYDROCARBON MIXTURES - Planche H. (My University, 1996)
The isothermal pyrolysis at 372°C, between 400 and 500 bars, of a paraffinic liquid hydrocarbon (natural physical conditions: 195°C, 1000 bars) has been performed over 3 months in order to observe composition changes and to calculate the total Gibbs energy of the fluid hydrocarbon mixtureG (t). The approach of a G minimum corresponding to a reversible equilibrium of the composition has been detected. This is consistent with the observation of a significant C11+ paraffin neo-formation flux after 2 months pyrolysis, and the overall stabilization trend for the fluid composition. The calculated stable composition of the saturates family is consistent with the one asymptotically reached after 1000 h of pyrolysis. This stable composition contains significant amounts of C6+ paraffins. Assuming the functionality of G in the time-composition space to be conserved when changing temperature from pyrolysis back to the initial fluid natural condition, the stable composition extrapolated at 195°C is that of a liquid hydrocarbon, very close to the natural oil used in the pyrolysis experiments. The observed concentration of most of molecular components of mature oils would thus be controlled by the effective equilibrium of a reversible chemical network. The reversibility of the oil saturates to gas + aromatics conversion is most probably the reason why C11+ paraffins may survive for as long as 100 Ma in the range 300 to 350°C as literature shows for hyper-mature rock extracts.